Re-repair after previous mitral valve reconstruction: handle with care!. (16th April 2020) - Trumello, Cinzia; Giambuzzi, Ilaria; Del Forno, Benedetto; Bargagna, Marta; Blasio, Andrea; Ruggeri, Stefania; Meneghin, Roberta; Schiavi, Davide; Nascimbene, Simona; Castiglioni, Alessandro; Alfieri, Ottavio; De Bonis, Michele
Abstract: OBJECTIVES: Patients with recurrent mitral regurgitation after surgical repair are currently treated with a re-repair procedure or valve replacement. The aim of this study was to compare outcomes of our series of patients who underwent re-repair versus replacement in this setting. METHODS: From 2003 to 2017, a total of 79 patients with recurrent mitral regurgitation underwent re-repair, group A (39), or replacement, group B (40). Mean follow-up was 7.4 ± 3.27 years (max 14.4). Inverse Probability of Treatment Weighting was used to create comparable distributions of the covariates; the Kaplan–Meier method was used for survival and competing risk analysis for time to cardiac death, time to recurrence of MR ≥3+ and MR ≥2+. RESULTS: A re-repair was possible in 49.4% of patients (39/79). At hospital discharge, residual MR ≥2+ was present in 5 patients in group A, and none in group B ( P  < 0.001). The paired overall survival at 8 years was 100% in the re-repair group and 96.5 ± 2.34% in the replacement group ( P  = 0.069). The cumulative incidence function of cardiac death, with non-cardiac death as competitive event, at 8 years was 0% in group A and 3.5 ± 2.34% in group B ( P  = 0.077). The cumulative incidence function of MR ≥3+ at 8 years was 29.2 ± 8.81% in group A and 0% in group B ( P  < 0.001). CONCLUSIONS: Recurrent significant mitral regurgitation after re-repair is not rare already at 8 years, but the survival tends to be worse after replacement. This finding calls for a very selective approach in pursuing a re-repair only when the intraoperative findings and the immediate results are very reassuring as far as long-term durability is concerned.